What constitutes the social in (social) sustainability? Community, society and equity in South African water governance. Issue 4 (3rd April 2023) - Hellberg, Sofie
ABSTRACT: This article explores the question of what constitutes the "social" in (social) sustainability. It applies a governmentality perspective and focuses especially on how social sustainability is understood in relation to the concepts of society and community . Furthermore, it investigates what social sustainability means, or could mean, in the specific context of water governance in South Africa – one of the most unequal countries in the world. This case study is based on original fieldwork in the country, conducted between 2017 and 2018. The theoretical exploration, together with the empirical study, demonstrate that there are two interrelated tensions between understandings of social sustainability, between approaches that place society/social cohesion in focus and those that emphasise community and between approaches that focus on basic needs and those that emphasise equal access. At stake here, between these different understandings, is the role of equity and to what extent social sustainability takes into account the situation of individuals and groups in relation to one another . Ultimately, the article raises the question of the (South African) elephant in the room: to what extent can large inequities between individuals and groups be accepted in a society considered to be (socially) sustainable?